2020
DOI: 10.1080/14728222.2020.1805734
|View full text |Cite
|
Sign up to set email alerts
|

Novel therapeutic targets for amyotrophic lateral sclerosis: ribonucleoproteins and cellular autonomy

Abstract: Introduction: Amyotrophic lateral sclerosis (ALS) is a devastating disease with a lifetime risk of approximately 1:400. It is incurable and invariably fatal. Average survival is between 3 and 5 years and patients become increasingly paralyzed, losing the ability to speak, eat, and breathe. Therapies in development either (i) target specific familial forms of ALS (comprising a minority of around 10% of cases) or ii) emanate from (over)reliance on animal models or non-human/non-neuronal cell models. There is a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 189 publications
(204 reference statements)
0
3
0
Order By: Relevance
“…The ALS-causing VCP mutations R155C and R191Q in this study did not show nucleocytoplasmic transport defects following cellular stress, despite a reduction in their nuclear-to-cytoplasmic ratios under basal conditions. ALS results from a wide variety of genetic insults, and multiple mechanisms are involved in the disease pathogenesis, accounting for the differences in nucleocytoplasmic defects [49]. Taken together, our findings suggest that the basal TDP-43 and FUS mislocalisation observed in VCP mutant MNs is not (at least initially) caused by failure of their nuclear relocalisation following cellular stress.…”
Section: Discussionmentioning
confidence: 63%
“…The ALS-causing VCP mutations R155C and R191Q in this study did not show nucleocytoplasmic transport defects following cellular stress, despite a reduction in their nuclear-to-cytoplasmic ratios under basal conditions. ALS results from a wide variety of genetic insults, and multiple mechanisms are involved in the disease pathogenesis, accounting for the differences in nucleocytoplasmic defects [49]. Taken together, our findings suggest that the basal TDP-43 and FUS mislocalisation observed in VCP mutant MNs is not (at least initially) caused by failure of their nuclear relocalisation following cellular stress.…”
Section: Discussionmentioning
confidence: 63%
“…Through this binding, ASOs are able to modify RNA processing and protein expression through distinct mechanisms. The benefit of this method for targeting SFPQ is that the ASO may be designed specifically to bind to the retained‐intron proportion of SFPQ , thereby preventing RBPs such as FUS and SFPQ from binding to the aberrantly retained intronic portion explored above while retaining the function of correctly spliced SFPQ 118 . Although it is unlikely that this is the only mechanism of FUS mislocalisation in ALS pathogenesis, it is potentially an important contributing factor 110 .…”
Section: Rna Homeostasis and Als Pathogenesismentioning
confidence: 99%
“…The benefit of this method for targeting SFPQ is that the ASO may be designed specifically to bind to the retained-intron proportion of SFPQ, thereby preventing RBPs such as FUS and SFPQ from binding to the aberrantly retained intronic portion explored above while retaining the function of correctly spliced SFPQ. 118 Although it is unlikely that this is the only mechanism of FUS mislocalisation in ALS pathogenesis, it is potentially an important contributing factor. 110 Building on the above study, Tyzack et al 119 identified an additional pool of >100 intron-retained transcripts within human ALS-mutant iPSCs that demonstrated increased cytoplasmic localization.…”
Section: Targeting Rna Processing As a Therapeutic For Alsmentioning
confidence: 99%